Pemanfaatan Sistem Informasi Akademik dan Media Video Pembelajaran Sebagai Penunjang Kinerja Guru - Belluano, Poetri Lestari Lokapitasari; Faradibah, Amalia; Saiman, La; AR, Fatimah; Kasmira, Kasmira (Vokasi Universitas Halu Oleo, 2021)
Academic Information System (xSIA) is a system that has one function to manage student data so as to provide convenience for teachers as the main users in recording the final grades of student learning outcomes each semester. The PKM program for teacher partners also provides technical training using the Snagit application to find out learning video material as an alternative method so that it can support teacher performance in the online teaching process. So that the Learning From Home (LFH) or Distance Learning Method can be implemented by school teachers at SDN No.133 Pari'risi Takalar. The training model applied uses the Preceptorship and Participatory training model. while the design phase of the application model used by Prototyping to graphically represent the workflow of the system. The objectives of this research are: 1) The existence of a web-based academic information system application, namely xSIA to report student assessments and application video tutorials. 2) Output in the form of the ILKOM Scientific Journal for the 2021 period UMI Computer Architecture or other Accredited journals. And 3) enrichment of teaching materials in Software Engineering courses.